Pembinaan Anggota dan Karyawan KUD Minarasa Batukaras: Meningkatkan Motivasi Kerja Karyawan dan Pemahaman Berkoperasi Anggota - Sir Kalifatullah Ermaya; Husnah Nur Laela Ermaya (E-Coops-Day, 2023)
The development number of cooperatives in Indonesia continues to increase rapidly, but there arestill many cooperative members and employees who do not understand the principles of cooperativesso many cooperatives are not active. One of the cooperatives in Pangandaran is KUD Minarasa,Batu Karas. The Community Service Team provides guidance in the form of material regarding motivation so that members can participate better and employees work more actively to improve their performance. Some of the motivational theories provided in this Community Service activity are the Hierarchy of Needs Motivation Theory, Two Factor Theory, X and Y Theories. Although there are many motivational theories in management science, in practice it is possible to motivate members and employees using a customized method. It is hoped that this training for members and employees will provide good input to members, employees, and all levels of management.